2021
DOI: 10.1101/2021.10.19.465049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sculpting rupture-free nuclear shapes in fibrous environments

Abstract: Cytoskeleton-mediated force transmission regulates nucleus morphology. How nuclei shaping occurs in fibrous in vivo environments remains poorly understood. Here a suspended nanofiber assay of precisely-tunable (nm-μm) diameters is used to quantify nucleus plasticity in fibrous environments mimicking the natural extracellular matrix. In contrast to the apical cap over the nucleus in cells on 2-dimensional surfaces, the cellular cytoskeleton of cells on fibers displays a uniform actin network caging the nucleus.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…We observe line tensions in the range 5-25 mN/m, which over a representative adhesion patch on fibers of 10 μm results in 50-250 nN force, in agreement with forces reported by our parallel-fiber network based Nanonet Force Microscopy 45 . The typical force per adhesion patch is measured to be in a similar range using soft gels (2-50 nN 46,47 ), fibrous networks (100-400 nN 31,45 ), and micropost arrays (1-80 nN 46,48,49 ). To visualize the spatial organization of cellular contractility, we developed force polarity maps that show the contractility 𝐶𝐶 𝜃𝜃 at an angle 𝜃𝜃 to the x-axis in a polar plot (Fig.…”
Section: Error Analysis Of Forces Estimated By the Inverse Formulationsupporting
confidence: 90%
“…We observe line tensions in the range 5-25 mN/m, which over a representative adhesion patch on fibers of 10 μm results in 50-250 nN force, in agreement with forces reported by our parallel-fiber network based Nanonet Force Microscopy 45 . The typical force per adhesion patch is measured to be in a similar range using soft gels (2-50 nN 46,47 ), fibrous networks (100-400 nN 31,45 ), and micropost arrays (1-80 nN 46,48,49 ). To visualize the spatial organization of cellular contractility, we developed force polarity maps that show the contractility 𝐶𝐶 𝜃𝜃 at an angle 𝜃𝜃 to the x-axis in a polar plot (Fig.…”
Section: Error Analysis Of Forces Estimated By the Inverse Formulationsupporting
confidence: 90%
“…We used suspended nanofibers that mimic the loose interstitial network found in vivo with large and small pore sizes to the extent that cells make contact with only single fibers. 52 We have recently shown that nuclei may lack apicobasal polarity, which causes a uniform distribution of proteins, including lamins, actin, and cytoskeleton, 53 which causes compression of the nuclei from all sides of the nanofiber. Thus, the nuclei of the cells attached to suspended nanofibers show considerable differences from the other in vitro systems with constrained apicobasal polarity, a potential reason for the difference in heterochromatin organization and dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by these results on two fiber systems, we enquired if there were any differences in the nucleus shape for cells migrating on single fibers. Confocal imaging revealed invaginations in the nuclear envelope at fiber-specific sites [46] . We examined the shape of local invaginations and found a remarkable difference between the WT and KO cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%